ГЛОБАЛІЗАЦІЯ ТА УКРАЇНСЬКІ КУЛЬТУРНІ ІДЕНТИЧНОСТІ: ПОЛІЦЕНТРИЗМ, ТОТАЛЬНІСТЬ, ХОЛІСТИЧНІСТЬ - ТИТАР, О. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
У нашій роботі досліджені українські культурні ідентичності в умовах глобалізації, визначені сумісні характеристики тотальних, холістичних та полікультурних ідентичностей. Поняття тотальної та холі стичної ідентичності говорить про різні рівні цілісності та фрагментованості сучасної глобалізованої ідентичності. Холі стична ідентичність характеризується єдністю аксіологічних та естетичних параметрів, розчиненню ідеальних конструктів у повсякденному, тотальна характеризується протиріччями між ідеалом та його втіленням, цінностями та їхнім втіленням. Тобто в глобалізованих ідентичностях ми можемо говорити про різні рівні синтезу та комунікативних практик. Титарь Е. В. ГЛОБАЛИЗАЦИЯ И УКРАИНСКИЕ КУЛЬТУРНЫЕ ИДЕНТИЧНОСТИ: ПОЛИЦЕНТРИЗМ, ТОТАЛЬНОСТЬ, ХОЛИСТИЧНОСТЬ В нашей работе исследованы украинские культурные идентичности в условиях глобализации, определены сущностные характеристики тотальных, холистических и поликультурных идентичностей. Понятия тотальной и холистической идентичности говорят о разных уровнях целостности и фрагментирования современной глобализированной идентичности. Холистическая идентичность характеризуется единством аксиологических и эстетических параметров, растворением идеальных конструктов в мире повседневного. Тотальная идентичность характеризируется противоречиями между идеалом и его воплощением, ценностями и их воплощением. Таким образом в глобализированных идентичностях мы можем говорить о разных уровнях культурного синтеза и разных коммуникативных практиках. Ключевые слова: идентичность, коммуникация, тотальность, холизм, поликультурность, глобализация, тотальная культурная идентичность, холистическая культурная идентичность. Tytar Olena GLOBALIZATION AND UKRAINIAN CULTURAL IDENTITY: POLYCENTRICITY, TOTALITY, HOLISTICS Space and time in the functioning of identity are not just a postmodern "space - time compression," or a specific sequence of events and "places", space and time are filled with events that got the valued differentiation. Based on these axiological characteristics the acceleration of time and centring operate near the determined key locations of space. Appear fuller and less filled with social meaning social plane, space, social attention and social neglect, resulting in information and social streams, creating new forms of centering. For example, the concept of Hannah Arendt draws attention to the fact that the state loses the capacity for such alignment, creating an "empty political space" that is deprived former influence on forming and functioning of cultural identities The concept of "individualized society" Z. Bauman is based on the consideration of cultural identities as a postmodern individualized, they survived the dismantling of the collective is the institutionalized framework of finding individuality. But, in our view, is not only dismantling of social institutions, including the state, but also the formation of new social institutions, more flexible than the old. Such institutions can be called (M. Castells terms) social and information flows, which are not less inclusive than the old institutions. In addition, our study has received considerable attention to the fact that for a holistic identity is not specific blurring concept of the center, and the existence of many centers - polycentricity. Here we use the metaphor of the network society in which there are a lot of sites and centers of gravity, and the decline in the value of one of the centers of communication in general, leads to a decline in the integral part of such a communication network. In our work Ukrainian cultural identity in the conditions of globalization is analyzed, defined the essential characteristics of a total, holistic and multicultural identities. The concept of total and holistic identity talk about different levels of integrity and fragmentation of modern globalized identity, about the different types of compounds of these identities with internal and external communication, the different levels of its functioning in social integration. Holistic identity is based on simultaneously, which provides the current level of technology and communications, and cyclically of the information society, correlate with the natural cycles. Total identity is based on the fragmentation and merging fragments of space-time in a specific sequence, which depends on the alignment of social (social needs, the rate of social processes). Total identity replaces the cyclic compound ephemeral time (instantaneous) and the eternal. Holistic identity characterized by unity axiological and esthetic parameters, dissolution ideal constructs in the everyday world. Total identity is characterized by contradictions between the ideal and its embodiment, values and their realization. Thus, in the globalized identities we can talk about different levels of cultural synthesis and different communicative practices. Key words: identity, communication, totality, holism, multiculturalism, globalization, total cultural identityl, holistic cultural identity.